Persepsi Mempengaruhi Rendahnya Pemakaian Kontrasepsi Implan - Akhmad, Reznita Adityani D; Saadong, Djuhadiah; Afriani, Afriani; Hidayati, Hidayati (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2022)
Indonesia, there are relatively few users of contraceptive implant methods compared to other types of contraception, although implants have a higher level of effectiveness than other contraceptives. The government has made various efforts but to no avail. The purpose of the study was to determine the factors that influence the low use of contraceptive implants at the Minasa Upa Health Center in Makassar City. The research method is an analytic survey with a